KAMPANYE KOMUNIKASI PEMASARAN DALAM MENINGKATKAN PERFORMA MEDIA DIGITAL JATENG POS SEBAGAI SOCIAL MEDIA SPECIALIST DAN CONTENT CREATOR AND CREATIVE - Eirene Yohana L. Tobing; Yohanes Thianika Budiarsa (Interaksi Online, 2026)
Digital transformation has challenged Jateng Pos to improve its digital media performance, which was hindered by low website traffic, audience reach, and social media engagement. This field project implemented an Integrated Marketing Communication (IMC) strategy through social media marketing, Instagram Ads, public relations, events, and digital campaigns, including Jangan Cuma Klik Judulnya, Creative News Challenge, and Jateng Pos Goes to School. The author served as a Social Media Specialist, Content Creator, and Creative. The campaign successfully increased Instagram reach (893 to 113,718), followers (3,763 to 4,670), engagement rate (0.03% to 10.62%), and referred website traffic (373 to 1,182). These results demonstrate the effectiveness of the integrated communication strategy in strengthening Jateng Pos’s digital presence and engagement with Generation Z audiences.